Pharmacodynamics and tolerability of repository corticotropin injection in healthy human subjects: A comparison with intravenous methylprednisolone. (10th September 2015) - Lal, Ritu; Bell, Stacie; Challenger, Rashida; Hammock, Vakessa; Nyberg, Mary; Decker, Dima; Becker, Patrice M.; Young, David
Abstract: Repository corticotropin injection (porcine adrenocorticotropic hormone [ACTH] analog) and intravenous methylprednisolone (IVMP) are used to treat inflammatory conditions such as multiple sclerosis (MS) exacerbations and rheumatoid arthritis. This multiple‐dose, randomized, crossover, open‐label study evaluated and compared pharmacodynamic outcomes in subjects who received ACTH analog (80 U subcutaneously) or IVMP (1 g) daily for 5 days. Specific outcome measures included IVMP and cortisol concentrations, total cortisol‐equivalent exposure, immune cell population changes, and tolerability. IVMP and ACTH analog increased granulocyte numbers and decreased lymphocyte counts; effects on both were significantly less pronounced with ACTH analog. Based on total cortisol‐equivalent exposure (assuming linearity), administration of 80 U of ACTH analog equates to 30 mg IVMP. Because IVMP doses significantly higher than 30 mg are usually required to treat MS exacerbations, the lower cortisol‐equivalent exposure of 80 U ACTH analog supports the hypothesis that efficacy of ACTH analog results from both steroid‐dependent and ‐independent properties. Adverse events were mild in severity; subject incidence for adverse‐event reporting was similar following both regimens. The clinical relevance of these findings in autoimmune disease populations is unknown and requires further evaluation.